Investigating the Empathic Skills of Physical Education Teachers - Şinoforoğlu Tolga; Balçıkanlı Gülfem Sezen (Sciendo, 2020)
Introduction: As one of the most important requirements for healthy communication, empathy is vital in a great many occupations. Various studies have investigated the importance and level of empathy in various occupation groups. One of the leading occupations requiring strong empathic skills is teaching. Teachers need empathy to create an effective learning environment, develop good communication with their students, and understand them well. The current study investigates the empathic skills of physical education teachers to evaluate various variables.